Effects of financial development on income inequality in East Java Province - Munawaroh Desty Anggraeni; Ris Yuwono Yudo Nugroho (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2020)
The research purposes are: (1) to determine the effect of financial sector development on income inequality in East Java Province, (2) to determine the effect of regional characteristics on income inequality in East Java Province. The study uses descriptive quantitative methods. The analysis method uses panel data regression with time series from 2013 to 2017 and cross-sections of 38 districts in East Java Province. The study results are as follows: (1) financial development has a negative and significant effect on income inequality, (2) the regional budget has a positive and significant effect on income inequality in East Java Province, (3) population density has a positive and significant effect on income inequality, (4) poverty has a positive and significant effect on income inequality, and (5) unemployment has no influence and is not significant in income inequality.